Efeitos do treinamento pliometrico na forca explosiva e potencia de meninas puberes practicantes de voleibol - Vilela, G.; Fernandes da Silva, S. (Revista Brasileira de Ciência e Movimento, 2017)
The aim of this study was to evaluate the effects of plyometric training (PT) on explosive strength 1 and power (PR) of the lower limbs in 72 pubertal girls volleyball players aged 12.18 ± 1.27 years, Height 1.56 ± 008 m, body fat 24.32 ± 6.77 and body mass = 48.18 ± 11.28 kg. All were in stage of pubertal maturation in the stage of pubertal maturation according to the method Tanner. Divided into two groups: Control Group - CG n = 48, held three sessions per week of volleyball and Experimental Group - EG n = 24, which held in addition of 3 weekly sessions of volleyball, more 3 weekly sessions of PT during 8 weeks, that comprised the multi jump, jump over hurdle and drop jumps with heights between 20 cm and 60 cm, the assessments of ES and PR occurred pre and post-training with an interval of 8 weeks. To assess the ES and PR the following procedures were used: SJ (squat jump), CMJ (Counter Movement Jump) and DJ (Drop Jump). The EG presented an improvement of 0.59 cm in SJ (19.12 ± 4.03 - 19.71 ± 3.93) which represents an increase of 3.08%, while in the CMJ the increase was 0.64 cm (19.88 ± 3.76 - 20.52 ± 4.26) which means an improvement of 3.21% between the pre and post training. The results of the GE presented improvements were not significant, which shows a positive effect of PT on the ES and PR in the pubertal girls practicing volleyball.